Rancang Bangun Sistem Informasi Administrasi Perhotelan Pada New Cahaya Hotel Sidoarjo - Moch. Reza Pahlevie; Henry Bambang Setyawan; Yoppy Mirza Maulana (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
New Cahaya Hotel is a company engaged in the field of tourism as an hotel in Sidoarjo. New Cahaya Hotel still using manual methods for daily administration, such as reservation, check in, check out, in house services, and making reports. This recording methods for a company that engaged in services can be not efficient, for example taking too much time to handling check in registration. It can be risky too for saving valueable informations. To overcome the problems above, researcher is designing and implementing an hotel administration information system. The result from this hotel administration system is hotel administration reporting. So, this system can overcome the company’s administration problem and give efficient and effective information.Keywords: information system, hotel administration system reporting